Affordability of nutritious foods for complementary feeding in South Asia - Ryckman, Theresa (Nutr Rev, 2021)
The high prevalence of stunting and micronutrient deficiencies among children in South Asia has lifelong health, educational, and economic consequences. For children aged 6–23 months, undernutrition is influenced by inadequate intake of complementary foods containing nutrients critical for growth and development. The affordability of nutrients lacking in young children’s diets in Bangladesh, India, and Pakistan was assessed in this study. Using data from nutrient gap assessments and household surveys, household food expenditures were compared with the cost of purchasing foods that could fill nutrient gaps. In all 3 countries, there are multiple affordable sources of vitamin A (orange-fleshed vegetables, dark leafy greens, liver), vitamin B(12) (liver, fish, milk), and folate (dark leafy greens, liver, legumes, okra); few affordable sources of iron and calcium (dark leafy greens); and no affordable sources of zinc. Affordability of animal-source protein varies, with several options in Pakistan (fish, chicken, eggs, beef) and India (fish, eggs, milk) but few in Bangladesh (eggs). Approaches to reduce prices, enhance household production, or increase incomes are needed to improve affordability.